Carl Andresen (1909-1985): ein protestantischer Kirchenhistoriker in seiner Zeit - Ritter, Adolf Martin (Zeitschrift für antikes Christentum, 2012)
The article sketches fundamental lines of the research and the person of Carl Andresen. Born in the north of Schleswig he remained a man between the boarders, between Patristics and Christian Archeology. This was the basis for his intensive work on the subject “Antiquity and Christianity”, as it can be observed already in his book about Celsus. Finally, the theological importance of Church History was stressed by Andresen. This lead him to a high estimation of “Dogmengeschichte”.